Broadband supercontinuum generation with femtosecond pulse width in erbium-doped fiber laser (EDFL) - Rifin, S.N.M.; Zulkifli, Mohd Zamani; Hassan, S.N.M; Munajat, Yusof; Ahmad, H (IOP Publishing, 2016)
We demonstrate two flat plateaus and the low-noise spectrum of supercontinuum generation (SCG) in a highly nonlinear fiber (HNLF), injected by an amplified picosecond pulse seed of a carbon nanotube-based passively mode locked erbium-doped fiber laser. A broad spectrum of width approximately 1090 nm spanning the range 1130–2220 nm is obtained and the pulse width is compressed to the shorter duration of 70 fs. Variations of the injected peak power up to 33.78 kW into the HNLF are compared and the broad spectrum SCG profiles slightly expand for each of the injected peak powers. This straightforward configuration of SCG offers low output power and ultra-narrow femtosecond pulse width. The results facilitate the development of all fiber time-domain spectroscopy systems based on the photoconductive antenna technique.